Influence of practice on visual reaction time - Tejas P Ghuntla; Hemant B Mehta; Pradnya A Gokhale; Chinmay J Shah (Wolters Kluwer Medknow Publications, 2014)
Background: The present study was aimed to see the effect of practice on visual information processing speed. Reaction time is one of the important physiological parameters, which gives information how fast and quickly person responses. Reaction is purposeful voluntary response to different stimuli as visual stimuli. Visual reaction time (VRT) is the time required to response to visual stimuli. Materials and Methods: The VRT was measured by the multiple choice apparatus in subjects. Simple reaction time and choice reaction time measured. Reaction time was measured in two sessions. In the first session, VRT was measured without practice of task and in the second session VRT was measured after practice of task. The results were statistically analyzed and were recorded as mean ± standard deviation and Student's paired t-test was applied to check the level of significance. Result and Conclusion: In the present study, we found that VRT was less after practice for both simple and choice VRT tasks. Reaction time decreases by practice. Skills can be improved by practice. In daily life majority of work is done by the use of visual information. By the practice of an important task time required for stimulus identification and response can be decreased. Practice is useful for driving vehicles. It is helpful to students, as they have identification of bones, instruments, graphs and viva questions in examination of various medical subjects. Hence by practice students can identify, understand and answer quickly.